Atitude do consumidor maduro em rela????o ?? ado????o de novas tecnologias. - Castro, Marcos Lencioni (2009)
The significant increase of aging population in the world along with technological advance in the modern society makes the adoption of new technologies by mature consumers an important factor of social inclusion and well being. This paper investigated through theoretical contribution of the consumer socialization the mature consumer attitude toward adoption of new technologies, it also tried to understand if this attitude is statistically significant in comparison to younger people and if it can be explained by the socialization process. The research took place with the attitude toward computer because of the inability to search all existing technologies and the fact that skills in using tools of information technology are becoming increasingly expected in the routine of human beings. Through a structured questionnaire was made a survey with 386 people using a convenience sample. Outcomes from the survey found that mature consumers attitude towards new technologies can not be explained by socialization process. The technique used for data analysis was the CHAID algorithm module from AnswerTree